An Inconsistent Canadian Provincial and Territorial Response During the Early COVID-19 Pandemic - Cyr, Amelie; Mondal, Prosanta; Hansen, Gregory (Frontiers in Public Health, 2021)
Objectives: According to the World Health Organization (WHO), an early and consistent international and national response is needed to control a pandemic’s spread. In this analysis, we evaluate the coordination of Canada’s early response to the coronavirus (COVID-19) pandemic in terms of public health interventions implemented in each provinces and territory. Methods: Retrospective data was obtained from publicly accessible websites maintained by federal, provincial and territorial governmental agencies. Consistent with WHO’s spreading of the disease pandemic action, individual and community-based public health interventions and policies were the focus. Time of intervention or policy, and COVID-19 cases per million at time of intervention was recorded for each province and territory. Results: Most public health interventions demonstrated wide time ranges of implementation across provinces and territories. At time of implementation, there were wide variations in the number of positive COVID-19 cases, suggesting that other factors may have been preferentially considered. Conclusions: Whether an earlier and more structured national approach would have lessened the pandemic’s burden is uncertain, calls for greater federal coordination and leadership should to examined.